Tepuk Sakinah and Family Resilience: an Evaluative Framework Within The Maqasid Al-Shariah Paradigm - Achmad Baidhowi; Shofiatul Jannah; Dwi Ari Kurniawati; Ahmad Shodiqin (MUSLIM HERITAGE, 2026)
Abstract This article explores Tepuk Sakinah as a means of internalizing the values of a harmonious family in response to high divorce rates, which indicate that premarital guidance should focus on preparing prospective couples to manage conflict, communication, finances, and family responsibilities. The objectives of this study are to analyze the relevance of the five pillars of Tepuk Sakinah to Maqasid al-Shariah, to describe its implementation in Marriage Guidance at the Jombang Subdistrict Office of Religious Affairs, and to formulate a realistic evaluation framework. This study employs a descriptive qualitative approach with a constructivist paradigm. The findings indicate that Tepuk Sakinah functions as a reminder of values during the closing session of Marriage Guidance, not as part of the marriage contract ceremony. Its five pillars align with the al-daruriyyat al-khams. Zawaj and Mitsaqan Ghalizan relate to Hifz al-nasl and Hifz al-din; Muasyarah bil maruf to Hifz al-nafs; Musyawarah to Hifz al-aql; and Taradin to Hifz al-nafs and Hifz al-mal. The evaluation framework is broken down into the orientation of Maqasid al-Shariah, micro-skills, core activities, and indicators suitable for implementation within a limited service duration. The Tepuk Sakinah evaluation is not sufficient to measure mere memorization of the pillars; rather, it must assess understanding of the values, readiness to address issues, and the applicability of the indicators. The implications of the findings suggest that Tepuk Sakinah is suitable to be positioned as a medium for the internalization of sakinah family values based on Maqasid al-Shariah.   Abstrak Artikel ini mengeksplorasi Tepuk Sakinah sebagai media internalisasi nilai keluarga sakinah dalam merespons tingginya angka perceraian yang menunjukkan bahwa pembekalan pranikah perlu diarahkan pada kesiapan calon pasangan dalam mengelola konflik, komunikasi, ekonomi, dan tanggung jawab keluarga. Tujuan penelitian ini adalah menganalisis relevansi lima pilar Tepuk Sakinah dengan Maqasid al-Shariah, mendeskripsikan operasionalisasinya dalam Bimbingan Perkawinan di Kantor Urusan Agama Kecamatan Jombang, serta merumuskan kerangka evaluasi yang realistis. Metode penelitian ini menggunakan pendekatan kualitatif deskriptif dengan paradigma konstruktivis. Hasil temuan menunjukkan bahwa Tepuk Sakinah berfungsi sebagai media pengingat nilai pada sesi penutup Bimbingan Perkawinan, bukan bagian dari prosesi akad. Lima pilarnya selaras dengan al-daruriyyat al-khams. Zawaj dan Mitsaqan Ghalizan berkaitan dengan Hifz al-nasl dan Hifz al-din, Muasyarah bil maruf dengan Hifz al-nafs, Musyawarah dengan Hifz al-aql, serta Taradin dengan Hifz al-nafs dan Hifz al-mal. Kerangka evaluasi diturunkan menjadi orientasi Maqasid al-Shariah, keterampilan mikro, aktivitas inti, dan indikator yang layak diterapkan dalam durasi layanan terbatas. Evaluasi Tepuk Sakinah tidak cukup mengukur hafalan pilar, tetapi perlu membaca pemahaman nilai, kesiapan merespons masalah, dan keterpakaian indikator. Implikasi temuan menunjukkan Tepuk Sakinah layak diposisikan sebagai media internalisasi nilai keluarga sakinah berbasis Maqasid al-Shariah. Keywords: Tepuk Sakinah; Maqasid al-Shariah; Marriage Guidance; Islamic Family Law.